Hiperglicemia en pacientes post operados tratados con tacrolimus en la Unidad de Trasplante Renal del Hospital Nacional Edgardo Rebagliati Martins- EsSalud, enero-junio 2017 - Chavez Ordoñez, Yelsin Wuendi (2019)
The purpose of this report is to determine post-operative hyperglycemia treated with tacrolimus as part of the immunosuppressive therapy of patients in the renal transplant unit of the Edgardo Rebagliati Martins-EsSalud National Hospital, January-June 2017. Edgardo Rebagliati Martins-EsSalud, January-June 2017 period. To this end, clinical histories of post-operated patients from the renal transplant unit were reviewed and the data were recorded in the data collection form, which included the immunosuppressive treatment scheme, established doses, serum concentrations of tacrolimus, glucose values. Hyperglycemia was defined as serum fasting glucose values greater than 110 mg / dL. It was observed that the hyperglycemia related to tacrolimus occurs the first month 25% of the patients developed hyperglycemia, of which 35% of the total patients was in the range 6-10 ng / dl, 35% of 11-15 ng / dl and 30% of 16-20 ng / dl; It should be noted that the total of patients who were 16-20 developed hyperglycemia indistinctly of the month. The patients treated with tacrolimus developed hyperglycemia that, as the months went by and its dose decreased, became reversible, showing hyperglycemia as a dose dependent